(untitled) (The NOUN Journal of Agricultural Research and Development (NJARD), 2025)
This study explored farmers awareness of information sources of climate smart agricultural (CSA) practices and adaptation strategies of climate change in Bayelsa and Delta States, Nigeria. It used multi-stage sampling technique to select 598 respondents for the study. The data were collected using questionnaire and interview schedule. It employed descriptive and inferential statistics to analyses the data the study. The findings revealed that a significant majority (77.09%) of farmers were aware of CSA practices, with personal observation (72.91%), friends (62.21%), relatives (52.01%), and radio (51.34%) identified as the primary sources of information. The study found a strong positive relationship between access to reliable information and increased awareness of CSA practices. However, farmers face numerous challenges, including inadequate finance (92.47%), labour scarcity (87.12%), limited access to technical knowledge (85.95%), poor infrastructure (52.17%), soil nutrient depletion (59.03%), pest infestations (64.21%), and rising costs (81.61%) which hinder the full adoption of CSA strategies. Despite these challenges, the study recommended the potential for greater adoption of CSA practices when farmers would be supported with reliable information, financial assistance, and improved infrastructure. The findings suggested that strengthening extension services, providing affordable inputs, and enhancing climate information systems could significantly boost farmers’ capacity to mitigate the impacts of climate change, thereby contributing to increased agricultural productivity and food security.